Mental Health Continuum—Short Form: Confirmatory Factor Analysis (CFA) of Competing Models with Adolescents from Portugal - Luís Loureiro; José Santos; Cândida Loureiro (European Journal of Investigation in Health, Psychology and Education)
The concept of positive mental health (PMH) and therefore mental well-being (MWB) have taken center stage over the last few decades. The Mental Health Continuum—Short Form (MHC-SF) is one of the most important tools for assessing MWB. This study aims to assess the psychometric properties and dimensionality of the Portuguese version of the MHC-SF by comparing three competing models. Methods: Between January and March of 2021, a survey was conducted with a convenience sample of 495 Portuguese adolescents aged 12 to 18 years, enrolled in grades 7 to 12. Descriptive statistics and bivariate statistical tests and measures associated with confirmatory factor analysis (CFA) were calculated. Results: The results of the CFA support the idea that the bifactor model fits the data better than the other competing models. The indices support unidimensionality, namely the explained common variance (ECV = 0.81), the Percentage of Uncontaminated Correlations (PUC = 0.69), and the omega hierarchical (ωH = 0.89), and point to the existence of a general MHC-SF factor. The scale showed high reliability (ω = 0.95) in the general factor. The MHC-SF has concurrent validity, correlating with other scales that assess aspects related to mental health and well-being. Conclusion: The results point to the adequacy of the bifactor model and suggest the existence of a general factor of PMH, confirming that the total score of the scale can be used.